Pedagogies to Enhance Learning for Indigenous Students
XII, 224 p.
Keywords: This book describes research undertaken by leading Australian researcher in Indigenous communities. While the chapters are Australian in their focus, the issues that are discussed are similar to those in other countries where there are indigenous people. In most cases, in Australia and internationally, Indigenous learners are not succeeding in school, thus making the transition into work and adulthood quite tenuous in terms of mainstream measures. The importance of being literate and numerate are critical in success in school and life in general, thus making this collection an important contribution to the international literature. The collection of works describes a wide range of projects where the focus has been on improving the literacy and numeracy outcomes for Indigenous students. The chapters take various approaches to improving these outcomes, and have very different foci. These foci include aspects of literacy, numeracy, curriculum leadership, ICTs, whole school planning, policy, linguistics and Indigenous perspectives. Most of the chapters report on large scale projects that have used some innovation in their focus. The book draws together these projects so that a more connected sense of the complexities and diversity of approaches can be gleaned.